200 SERUM MARKER OF FIBROSIS I IS THE STRONGEST INDEPENDENT PREDICTOR OF DIASTOLIC FUNCTION IN PATIENTS WITH ADVANCED SYSTOLIC HEART FAILURE. Issue 1 (1st January 2007) - Roongsritong, C.; Sadhu, A.; Pierce, M.; Simoni, G.; Moeller, J.; Simoni, J.
Abstract : Background: Severe diastolic dysfunction, known as restrictive filling pattern, has been correlated with worse outcome in patients with advanced systolic heart failure. However, the degree of diastolic dysfunction in these patients is highly variable. The major determinants of diastolic function in patients with advanced systolic heart failure have not been well described. Methods: We enrolled 40 patients with heart failure and left ventricular ejection fraction (LVEF) < 35%. All patients underwent a standard transthoracic echocardiography to assess left atrial (LA) size, left ventricular end-diastolic dimension (LVEDD), transmitral Doppler peak early (E) and late diastolic velocities (A), deceleration time (DT), tissue-Doppler imaging-derived mitral annular early (E') and late (A') diastolic velocities. Diastolic function was classified based on both mitral Doppler flow pattern and tissue Doppler of mitral valve annulus. Serum carboxy-terminal peptide of procollagen type I (PICP), a marker of cardiac fibrosis, was determined by an enzyme-linked immunosorbent assay (Takara Inc.). Parametric and nonparametric tests were used when appropriate to determine independent predictors of diastolic function; p values of .05 or less were considered significant. Results: Mean age was 58.7 ± 13.9 years. Mean LVEF was 25.1 ± 6.4%. Female and ischemic etiology of systolic dysfunction was present in 28% and 48%, respectively. Mean PICP levels were significantly higher in patients with severe diastolic dysfunction (DD) versus the nonsevere group, 1, 308.31 ± 466.79 ng/mL versus 864.97 ± 366.19 mg/mL, respectively ( p < .0029). Univariate analysis found a significant relationship between the severity of diastolic dysfunction and PICP, age, and LA size but not with LVEF, LVEDD, race, gender, or serum creatinine. Multivariate analysis found only PICP ( p = .004) and age ( p = .029) to be independent predictors of diastolic dysfunction severity. Conclusion: In patients with advanced systolic heart failure, PICP, a serum marker of fibrosis, is significantly higher in those with severe diastolic dysfunction. Among parameters tested, PICP is the strongest independent predictor of diastolic function.